Congestion management under peer-to-peer energy trading scheme among microgrids through cooperative game. (April 2022) - Wang, Xiaoyu; Xu, Tao; Mu, Yunfei; Wang, Zibo; Deng, Youjun; Zhang, Tao; Jiang, Qian; Zhang, Yaqing; Jia, Hongjie
Abstract: The peer-to-peer (P2P) energy trading among microgrids (MGs) can promote the renewable energy accommodation of network while maximizing the benefits of their own. However, unregulated trade behavior may cause network congestion which affect the safe and stable operation of the system. To this end, this paper proposes an effective congestion management method under P2P energy trading of MGs based on cooperative game strategy. For a congestion caused by several MGs, the Shapley value is firstly used to allocate the congestion marginal contribution. Then, a congestion price coefficient is optimally determined by minimizing the overall congestion cost while maximizing the overall revenue of all MGs, the MGs who are cost-sensitive are advised to make a change on their trading scheme. Taking a system composed of 4 MGs as an example, simulation study is finally conducted to validate the effectiveness and applicability of the proposed methods.